The difference in parental financial socialisation across parental income level - Adam Ndou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The effect of parental income on parental financial socialisation is increasingly becoming important. The objective of this study was to determine the difference in parental financial socialisation across parental income levels. This study was guided by financial socialisation theory which is not only about learning financial skills, attitudes, standards, norms, and behaviours from childhood through adolescence, but is more concerned about what the socialisation process contributes to the overall financial well-being of individuals. Design/methodology/approach: Quantitative research approach was adopted for this study. Self-administered questionnaire was used to collect data among 500 young adults in South Africa. Descriptive statistics, Levene's test, Welch robust test, Tukey HSD test and ANOVA were used to analysed data. Four hypotheses were tested. Parental financial socialisation was measured through parental financial behaviour, parental financial monitoring, parental financial discussions, and parental financial communication. Findings: The results showed that there was a significant difference in Parental financial behaviour, parental financial monitoring, parental financial discussions, and parental financial communication across Parental income. Therefore, the overall results indicated that there was a significant difference in Parental financial socialisation across Parental income. Research limitations/implications: Due to the low levels of general literacy among the respondents, which negatively affected data collection; some young adults did not understand the questionnaire and withdrew from participating in the study. Furthermore, even though confidentiality and anonymity were guaranteed, respondents were reluctant to participate in the study. They feared exposing their financial position and displayed a lack of trust. Originality/value: The current study contributed to the body of knowledge differently to the previous studies because it focused on parental financial socialisation of young black African adults in rural and low-income area This study is the first to investigate the difference in parental financial socialisation across parental income levels. This makes this study so important and warrant that it should be carried out to provide the much-needed results that could help to improve parental financial socialisation across all income levels.
Keywords: D14; G51; G53; 330; Financial discussions; Parental income; financial monitoring; financial behaviour; financial communication